Role of Research in UMSEP - John Moore (Journal of Modern Languages)
This paper outlines the contribution that research made to the project and tries to indicate the particular style of research that the UMSEP team evolved. UMSEP was from the outset a research-based project. The paper reveals that the UMSEP materials are influenced strongly by accompanying research but that the final value of the materials depends on the ways in which the writers' creativity has been brought to bear on that research.